Automated finite element modelling of 3D woven textiles - Zeng, Xuesen; Long, A.C.; Clifford, M.J.; Probst-Schendzielorz, S.; Schmitt, M.W. (2011)
The advance of 3D fabric technology allows tailored material structure in different directions for optimised performance. 3D fabrics open up increasing applications in automotive, medical, energy and many other areas. This paper explores highly automated techniques to simulate 3D fabric geometry and mechanical behaviour. The basis of the work starts from TexGen,an open source software package developed at the University of Nottingham. A complex variety of 3D fabrics can be defined as subclass functions from base functions for individual yarns, crosssections and yarn paths. The 3D fabric geometry can be generated automatically in TexGen using a script given a number of parameters. From this geometrical model, an automated procedure is followed to create an input file for finite element analysis. Yarns are meshed with hexahedral and wedge elements. The input file contains the mesh, element orientations, material definitions, contact surfaces and definitions, periodic boundary conditions and loading steps. Once the FEA simulation is completed, the nodal displacement data are parsed into TexGen to build the deformed 3D fabric geometry. The deformed geometry model can then be used for further analyses, eg. to predict permeability or composite mechanical properties. An example for a complex three layer woven fabric is demonstrated.